THE IMPACT OF GUIDED WRITING TECHNIQUE TO DEVELOP STUDENTS’ ESP WRITING SKILLS IN BALIKPAPAN STATE POLYTECHNIC - Elisabeth Milaningrum; Lilik Damayanti; Abdul Gafur (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2018)
As an action research in nature, the research aimed to test the progress of the students’ ESP writing skills when guided writing technique is implemented in writing class and to know the ESP students’ attitude towards guided writing technique. This action research is conducted in two cycles. In collecting the data, the researcher uses qualitative and quantitave technique. The qualitative data are obtained from observation, interview, and test analysis. The qualitative data are supported by quantitative data that are the mean score of students’ pre-test and post-test on ESP writing. The procedure of guided writing which is implemented in ESP writing class are model paragraph, comprehension questions, language based exercises, oral composition, and written composition. After the analysis of data collected through test items, it was seen improvement in students’ ESP writing skills in post-test than in pre-test. The students have shown their improvement such as they are able to construct sentences correctly. They could use appropriate language use when created the pattern of tenses, article, preposition, pronoun, conjunction, and part of speech and also they used better mechanical aspects in writing like capitalization, punctuation, and spelling in post-test than in pretest. Moreover, they can use correct ESP diction on their writing after implemented this technique. The ESP students’ attitudes also were enthusiastic and more active involved in ESP writing class.